VET Data Report Germany 2013 : facts and analyses accompanying the Federal report on vocational education and training - selected findings - Le Mouillour, Isabelle [Herausgeber]; Friedrich, Michael [Herausgeber] (Bundesinstitut für Berufsbildung, 2014)
"This English version of the 2013 Data Report provides a selection of the main findings. The first two chapters present the current situation in initial vocational training and in continuing vocational training as well as highlighting the changes which have taken place over the course of time. Chapter 3 ('In focus') deals with the development and use of digital media in VET as a thematic priority. Chapter four widens the perspective to the international context with issues such as youth unemployment, recognition and mobility." (Hrsg., BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; S 1.3 Berufliche Erstausbildung; S 1.3.1 Ausbildung im Dualen System; S 1.5.2 Berufliche Weiterbildung; L 4.1.2 Elektronische Medien; I 1 Internationale Berufsbildung; G 1.3.3.3 Mobilität; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; Berufsbildungsbericht; Berufsbildungsstatistik; Berufsbildungspolitik; Berufsausbildung; Ausbildungsstellenmarkt; Berufliche Weiterbildung; Digitale Medien; Internationale Zusammenarbeit; Jugendarbeitslosigkeit; Mobilität; Anrechnung von Bildungsleistungen; Indikatoren